Mimari eleştiri metinlerinde parça ve bütün ilişkisinin yapısalcı yöntem ile aranması: Pompidou örneği - Aktaşlı, Arif (Fen Bilimleri Enstitüsü, 2020)
Mimari eleştiri metinlerinde parça ve bütün ilişkisi şu şekilde anlatılabilir; Bir eleştiri metninin içerdiği birçok okuyan tarafından farklı yorumlanabilir. Eleştiri metinleri bir tanımlamadan ziyade, eleştirmenin kendi doğrularını aktardığı bir okumadır. Eleştiri metinlerinin hem bir yazılma süreci hem de bir okunma süreci Mimari eleştiri metinlerinin mimarlık alanında üzerinde durulması gereken kritik bir mesele olması fikrinden yola çıkılarak bu tez yazıldı. Araştırma boyunca mimari eleştiri metinlerinin birer anlam bütünü olduğu gerçeği yok sayılmayarak incelemeler ile mimari eleştiri metinlerine dönük tanımlamalar yapıldı. Mimari eleştiri metinlerinin sistematik bir incelemeyle değerlendirilebilirliğinin arandığı bu çalışmada eleştiri metinlerinin öğeleri tanımlandı. Kavramsal tanımlamalar ile parça ve bütün ilişkisinin eleştiri metnilerindeki varlığı öznellik, nesnellik, doğru ve gerçek kavramlarıyla tanımlanabilir. olduğunu bilmek gerekir. Eleştirmenin kendi gözlem ve birikimiyle öznel yargılara vardığı metin onun mimariyi veya mekânı nasıl okuduğuyla alakalıdır. İkinci aşamada ise okuyucu eleştiri metnini kendi birikimiyle okur. Metnin her cümlesine aynı mesafe ile yaklaşmaz. Metinde kaybolur. Üçüncü aşamada ise okunan metin okuyucunun zihninde bir takım doğrular canlandırır. Algıda değişen bilgiler bütün farklı görme biçimlerinin çakışmalarıyla gerçekleşir ve bu algı kimi zaman anlık kimi zaman ise gelişmekte olan bir sürece tekabül eder; ancak en sonunda öznel bilgiler ile oluşturulan bütün metinler her okuyucu tarafından farklı öznel yargılarla anlam kazanır. Her okuyucunun algısında bir dünya oluşur. Bu dünya ne geçicidir ne de kalıcıdır. Bu dünya bilginin oluşmasında yol gösterici bir algıdır. Metin okuyucunun zihninde bu şekilde canlanır. Öznel bilginin nesnelliği yıkmadığı gerçeğiyle, bilginin defalarca üretilebildiği, eleştiri metinlerinin görülen ile algılanan arasında ilişki katmanları oluşturduğu bu çalışmanın üzerinde durduğu durumdur. Yazar ve okuyucu arasında gerçekleşen bu ikili okuma şekli mimari eleştiri metinlerinin de parça odaklı söylemler olabileceğine ışık tutmuştur. Mimari eleştiri metinlerinde aranan parçalar ile metnin içeriğine dair çıkarımlar yapabilme imkanı bulunur. Parça yazarın yapının bir kısmını işaret etmesiyle kendini gösterir. Parçalar yapının bütününü oluşturan bütün yapı elemanları veya olgularıdır. Parça tanımının mimari eleştiri metinlerinde aranmasının sebebi eleştiri metinlerinde aktarılan bütün olguların analizini yapabilmektir. Mimari eleştiri metinleri eleştirmenin kendi doğrularıyla gösterdiği parçaların bütünüdür. Parçaların doğru şekilde analizi mimari eleştiri metinlerinin anlamına da yaklaşmayı sağlar. Tezin amacı mimari eleştiri metinlerini parçalamak değildir. Hedeflenen olgu mimari eleştiri metinlerindeki parçaları görerek bir eleştiri metnindeki parametreler arasındaki ilişkileri anlamaktır. Bu tezde bir mimari eleştiri metninin aktardığı olgulardan, öznelliğinden, bilginin dönüşümünden, eleştirilen eserin parametrelerine kadar gerçekleşen süreç incelendi. Çalışma boyunca yapısalcı bir yöntem ile mimarlık ve mimari eleştiri metinlerini değerlendiremeye dönük parametreler belirlenmeye çalışıldı. Elde edilen bu parametreler ile eleştiri metinlerinin içerdiği değerler anlaşılmaya çalışıldı. Yapısalcığın bir değerlendirme yöntemi olarak kullanıldığı bu çalışma bir metnin içeriğini görmeyi hedefler. Bu mimari eleştiri metinlerini değerlendirmekten ziyade anlamaya dönük bir araştırmadır. Eleştiri metinleri bir anlam taşır. Yazarın konuya bakışıyla ortaya çıkardığı eleştiri metninin bir bütün olduğu unutulmamalıdır. Bir anlam bütünü olarak eleştiri metinlerinde anlamını bozacak bir parçalamaya gidilmeden tez boyunca eleştiri metinlerinin bütünü analiz edilir. Bahsedilen parçalar bütünü oluşturan olgulardır. Parametre ve değerler ise bir inceleme yöntemidir. Bu yöntem tez boyunca hafızada tutularak eleştiri metinlerinde herhangi bir kıyasa veya onaya yer verilmedi. Bu parametreler literatür taramasıyla yapıyı oluşturan bütün birimler ve çevredeki bütün nesnelerin niteliklerini belirten sınıflandırmalardan oluşur. Doğal ve kültürel bağlam altında bütün olgular gruplandırıldı. Bu sınıflandırma sonucu seçilen eleştiri metinlerinin yapının hangi niteliklerini ön plana çıkardığı görülmüştür. Sınıflandırılmanın uygulanacağı eleştiri metinleri seçilirken yapının özellikleri arasında güncelliğini yitirmemiş, hakkında çok sayıda eleştiri metni yazılmış, farklı tartışmaların ürünü olmuş bir bina seçildi. Alan çalışmasında Pompidou binası bütün tarihi süreci ve güncelliğiyle seçilerek, onun üzerine yazılan dokuz eleştiri metni incelenmiştir. Bütün bu metinlerin anlam bütünlüklerine değinilmeden onların içeriğinin yoğunluklarına değinildi. Yapısalcı bir yöntem ile oluşturulan parametre tablosunun içeriği eleştiri metinlerinde arandı. Sistematik bir inceleme yöntemiyle eleştiri metinlerinin çözümlemesi yapıldı. Çalışma sonucunda ise araştırma boyunca elde edilen bulgular, mimari eleştiri metinlerinin içerebileceği potansiyeller ve çalışma alanlarını tartışmaya dönük bir takım sorular çıkartıldı. Bu sorular bu çalışmanın üzerine bağımlı veya bağımsız birçok çalışmanın içeriği olabilir. Bu sınıflandırma yöntemi ile bahsi geçen değerlerin varlığı tespit edilmiştir. Bu analiz ile eleştiri metinlerinin içeriğinin bütün parçalarına dair nitelikler ortaya çıkarıldı. Araştırma sonucunda, eleştiri metinleri ile yapının parçalara ayrıldığı ve birden çok değerden oluştuğu görülmüştür. Tezin amacı ortaya çıkan değerler ve parçasal gösterimler ile eleştiri metnine olan bakışın sistematik olarak incelenmesinin öğretileridir. Çıkarılan bulgular ile eleştiri metinlerinin yazımından okunmasına kadar olan süreçte mimari eleştiri metinlerinin bir sistem ile incelenebilirdiği sorgulandı. Unutulmamalıdır ki mimari eleştiri metinleri birer anlatım tekniğidir ve hem eleştirmenin hem de okuyucunun gerçekleştirdiği birer okumadır. Bu sonsuz bir süreçtir.

This thesis has been written based on the idea that architectural criticism texts are a critical issue to be addressed in the field of architecture. Throughout the research, the fact that the texts of architectural criticism are a whole of meaning are not ignored, and some definitions were made with examinations. The reason for searching the part and the whole relationship is that the architectural criticism texts cause a different communication. This interaction can be summarized as follows; The content of a review can be interpreted differently by many readers. Criticism is a reading in which the critic conveys his own truths rather than a description. At this point, it is necessary to know that the text of criticism of the place is both a writing process and a reading process. The text that critics make subjective judgments through their own observation and accumulation is related to how they read architecture or space. In the second stage, the reader reads the text of criticism with his own knowledge. It does not approach each sentence of the text with the same distance. It disappears in the text. In the third stage, the text reads a number of verifications in the mind of the reader. The information that changes in perception occurs through the overlaps of all different forms of vision, and this perception sometimes corresponds to an instant and sometimes a developing process; however, at the end, all texts created with subjective information gain meaning by different subjective judgments by each reader. A world is formed in the perception of every reader. This world is neither temporary nor permanent. This world is a guiding perception in the formation of knowledge. This is how the text comes to life in the reader's mind. This study emphasizes the fact that subjective knowledge does not destroy objectivity, that knowledge can be produced many times and that the texts of criticism create layers of relationship between what is seen and perceived. This dual reading between the writer and the reader has also shed light on the architectural criticism texts that can be part-oriented discourses. In architectural criticism texts, it is possible to make inferences about the content of the text. The piece is manifested by the author pointing out part of the structure. Parts are all structural elements or phenomena that make up the whole structure. The reason why the part definition is searched in the architectural criticism texts is to analyze all the facts conveyed in the criticism texts. Architectural criticism texts are the whole parts of the criticism's own truths. Accurate analysis of parts also provides an approach to the meaning of architectural criticism texts. The aim of the thesis is not to break up architectural criticism texts. The aim is to understand the relationships between the data in a criticism text by seeing the pieces in the architectural criticism texts. In this thesis, the process that takes place from the facts conveyed by an architectural criticism text, its subjectivity, the transformation of knowledge to the parameters of the criticized work is examined. Throughout the study, a set of parameters were determined to evaluate architectural criticism texts using structuralist approach. Selected parameters is a classification to reach values and parts of the criticism texts mention. This study, where structuralism is used as an evaluation method, aims to show values and parts of the texts. This is a system for understanding rather than evaluating architectural criticism texts. Criticism texts make sense. Revealing the meaning is subjective, but reaching the content of the meaning is an objective study. This equation was kept in memory throughout the thesis and no comparison or approval was included in the criticism texts. These parameters consist of the literature review and all the units that make up the structure and the classifications that indicate the characteristics of all the objects in the environment. All cases are grouped under natural and cultural context. As a result of this classification, it has been seen which characteristics of the criticism texts highlight the structure. While selecting the criticism texts to be used for classification, a structure that has not lost its validity among the features of the building has been written, a lot of criticism texts have been written and a structure that has been the product of different discussions has been chosen. In the field study, the Pompidou building was selected with its entire historical process and timeliness, and nine critical texts written on it were examined. Without mentioning the integrity of the meaning of all these texts, their densities are mentioned. The content of the parameter table created by a structuralist method was sought in criticism texts. Critical texts were analyzed with a systematic review method. As a result of the study, some questions were raised to discuss the potentials, findings obtained during the research and fields of study of architectural criticism texts. These questions may be the content of many studies that are dependent on this study or independent. With this study, the meanings of the values that the criticism texts convey in the information about a place and the parts they point to were investigated. With the structuralist method applied throughout the thesis, the analysis of the object of the criticism texts from the whole to the piece was carried out. The existence of the mentioned values was determined by this classification method. There are similarities and differences between criticism texts according to the density of the parameters. Evaluation and analysis of criticism texts carried out with parameters provided sentence and word-oriented analysis of criticism texts that have the meaning of meaning. With this analysis, qualities regarding all parts of the content of criticism texts were revealed. As a result of the research, it has been seen that the criticism texts are divided into pieces and consist of multiple values. The expressions of these reached parts and values have never been compared and confirmed. The reason for this is that it is not a target to approve or criticize the text of the criticism. The aim of the thesis is to teach the systematic analysis of the view of the criticism text with the emerging values and partial representations. It has been questioned that the architectural criticism texts can be examined with a system in the process from the writing of the criticism texts to the findings. It should be remembered that the texts of architectural criticism are expression techniques and are readings by both the critic and the reader. This is an endless process.
Searching the relationship between piece and whole with structuralism as a method in architectural criticism texts: Example of pompidou
Tez (Yüksek Lisans)-- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2020
Keywords: Mimari eleştiri; Architectural criticism